2021
DOI: 10.3389/fneur.2021.690008
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Daytime Sleepiness in Obstructive Sleep Apnea Patients Treated With Continuous Positive Airway Pressure: Data From the European Sleep Apnea Database

Abstract: Excessive daytime sleepiness (EDS) is a symptom of obstructive sleep apnea (OSA) that resolves under treatment with continuous positive airway pressure (CPAP). In some patients, sleepiness persists despite CPAP treatment. We retrospectively analyzed data on subjective residual EDS, assessed as an Epworth Sleepiness Scale score (ESS) >10, in patients from the European Sleep Apnea Database (n = 4,853, mean age ± SD 54.8 ± 11.8 years, 26.1% females), at baseline and at the first visit (median follow-up: 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…Using our expanded sleepiness characterisations, nearly 43% of patients’ adherent to PAP therapy had persistent sleepiness symptoms. In contrast, 26% of participants had persistent sleepiness based solely on an ESS score of >10, which is in agreement with results from a recent multicentre study on 4,852 PAP‐treated patients with OSA reporting 28.2% of the population had persistent sleepiness (Bonsignore et al, 2021). Two other recent prospective studies on persistent sleepiness found a lower proportion, with only 12%–13% of the study populations having an ESS score of >10 (Gasa et al, 2013; Pépin et al, 2009).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Using our expanded sleepiness characterisations, nearly 43% of patients’ adherent to PAP therapy had persistent sleepiness symptoms. In contrast, 26% of participants had persistent sleepiness based solely on an ESS score of >10, which is in agreement with results from a recent multicentre study on 4,852 PAP‐treated patients with OSA reporting 28.2% of the population had persistent sleepiness (Bonsignore et al, 2021). Two other recent prospective studies on persistent sleepiness found a lower proportion, with only 12%–13% of the study populations having an ESS score of >10 (Gasa et al, 2013; Pépin et al, 2009).…”
Section: Discussionsupporting
confidence: 88%
“…We found that the non-sleepy phenotype had the highest pro- (Bonsignore et al, 2021). Two other recent prospective studiesonpersistentsleepinessfoundalowerproportion,withonly 12%-13%ofthestudypopulationshavinganESSscoreof>10 (Gasa et al, 2013;Pépin et al, 2009).…”
Section: Qol Chronotype and Comorbiditiessupporting
confidence: 45%
“…[10][11][12] Obstructive sleep apnea is highly prevalent, with recent general population studies indicating that 20% to 30% in men and 10% to 15% in women have moderate or severe sleep-disordered breathing. 13,14 Excessive daytime sleepiness (EDS), a major symptom of OSA, is reported in approximately 25% to 50% of OSA patients 15 and studies have shown that EDS while driving is an important factor in road accidents or work-related accidents. 13,16 While OSA has been recognized by the European Respiratory Society (ERS) as a risk factor for road accidents, 13 there is still uncertainty about the relative importance of OSA severity indices of OSA, and the degree of sleepiness as a risk factor for accidents.…”
Section: Introductionmentioning
confidence: 99%
“…Results in patients using mandibular advancement devices were similar to those in patients using CPAP [60]. Studies agree that a high ESS at baseline increases the risk of remaining sleepy on CPAP treatment [47,54,57,60,62]. As for the impact of OSA severity assessed as AHI, mild-moderate rather than severe OSA was more often associated with RES [47,56,57].…”
Section: Eds In Treated Osa Patientsmentioning
confidence: 55%
“…One multicentre randomised controlled trial assessed EDS monthly for the first 3 months of CPAP use, and showed a progressive decrease in its prevalence from 60% to 17%, together with significant sleep disruption during CPAP treatment documented by actigraphy [53]. The majority of studies were observational, either multicentre [5,[54][55][56][57] or single-centre [47,53,[58][59][60]. These studies reported a variable prevalence of EDS in treated OSA patients, and follow-up duration varied from 3 to 24 months.…”
Section: Eds In Treated Osa Patientsmentioning
confidence: 99%